Lactylation and viral infections: A novel link between metabolic reprogramming and immune regulation. - Shanshan Chen; Tongxue Qin; Shengrui Luo; Fengyi Wang; Feirong Chen; Hailun Wei; Yuting Wu; Rongfeng Chen; Wudi Wei; Jingzhen Lai; Hao Liang; Li Ye; et al. (PLoS Pathogens, 2025)
Post-translational modifications (PTMs) regulate protein structure, function, and interactions, playing pivotal roles in cellular processes and disease progression. Lactate, a byproduct of the Warburg effect, accumulates excessively during viral infections and functions as a signaling molecule, disrupting mitochondrial antiviral-signaling protein activity and facilitating viral immune evasion. Lactylation, a recently identified PTM derived from lactate metabolism, links cellular metabolism and immune regulation by modulating gene expression and metabolic reprogramming. It also serves as a mechanism for viruses to modulate host immunity. Despite its emerging importance, its role with respect to viruses infecting humans and animals remains poorly understood. Investigating its impact on metabolic, protein modifications, and immune signaling may reveal novel immune evasion strategies and therapeutic targets. This review aims to provide an overview of the fundamental features and regulatory functions of lactylation, explore its association with viral infections, and offer insights into how lactylation influences metabolic and immune responses during virus-host interactions.